Delphi consensus statement: Quality indicators for Inflammatory Bowel Disease Comprehensive Care Units. (1st March 2014) - Calvet, Xavier; Panés, Panes Julián; Alfaro, Noelia; Hinojosa, Joaquin; Sicilia, Beatriz; Gallego, Marta; Pérez, Perez Ildefonso; Lázaro y de Mercado, Lazaro y de Mercado Pablo; Gomollón, Gomollon Fernando; ,; Aldeguer, Xavier; Alós, Rafael; et al.
Abstract: Background and aims: While it is commonly accepted that Inflammatory bowel disease (IBD) Comprehensive Care Units (ICCUs) facilitate the delivery of quality care to Crohn's disease and ulcerative colitis patients, it remains unclear how an ICCU should be defined or evaluated. The aim of the present study was to develop a comprehensive set of Quality Indicators (QIs) of structure, process, and outcomes for defining and evaluating an ICCU. Methods: A Delphi consensus-based approach with a standardized three-step process was used to identify a core set of QIs. The process included an exhaustive search using complementary approaches to identify potential QIs, and two Delphi voting rounds to select the QIs defining the core requirements for an ICCU. Results: The consensus selected a core set of 56 QIs (12 structure, 20 process and 24 outcome). Structure and process QIs highlighted the need for multidisciplinary management and continuity of care. The minimal IBD team should include an IBD nurse, gastroenterologists, radiologists, surgeons, endoscopists and stoma management specialists. ICCUs should be able to provide both outpatient and inpatient care and admission should not break the continuity of care. Outcome QIs focused on the adequate prophylaxis of disease complication and drug adverse events, the need to monitor appropriateness of treatment and the need to reinforce patient autonomy by providing adequate information and facilitating the patients' participation in their own care. Conclusions: The present Delphi consensus identified a set of core QIs that may be useful for evaluating and certifying ICCUs.